Riding With Responsibility: Meningkatkan Kesadaran Anggota Klub Motor Tentang Dampak Negatif Fatherless Pada Pertumbuhan Emosi Anak - Pitaloka, Whilis (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2025)
The loss of a father figure, or fatherlessness, is one of the factors that often escapes attention, yet it has a profound impact on a child’s emotional development. This community service program aimed to enhance the awareness of motorcycle club members regarding the essential role of fathers in the growth and development of children, as well as the negative consequences that may arise in the absence of that role. The methods employed included interactive counseling, group discussions, and self-reflection activities involving motorcycle club members in Pontianak City. The results demonstrated an improvement in participants’ understanding of the issue of fatherlessness, as indicated by shifts in attitudes and commitments to enhancing communication patterns and their presence in their children’s lives. This initiative is expected to serve as a simple model for other communities in fostering broader social awareness related to family issues.